Learning styles performed by the vocational high school students of SMKN 1 Rantepao - rigel sampelolo (Teaching English as a Foreign Language Overseas Journal, 2017)
This research intended to find out the comprehensive description about learning styles performed by the Vocational high school students at SMKN 1 Rantepao. The instrument of thisresearch was questionnaire. The population in the study involved 30 students consisting of 10 students in each grade level. The result of the research showed that the dominant learning style of 30 students was Auditory learning style.